Effectivity and Efficiency of Regional Property Management Results and Financial Performance - Thafaki, Tasyaa'u Mulka (Universitas Negeri Semarang, 2018)
The purpose of this research to determine the level of efficiency and results that reflect the performance and financial performance of BUMD in Semarang City, period 2014-2016. The type of data used is secondary data, using data analysis through DEA analysis and interview method. The results showed that PDAMs and RPH & BPH in 2014 still met the level, with a value of 82.4% and 62.6%. In 2015, as a whole, BUMD has achieved the value of efficiency and effectiveness. In 2016 RPH & BPH companies have not been able to reach the level of 8.1%. The level of appeal in the 2014 and 2015 BPR BKK will jointly achieve a joint achievement level of 89.5% and 93.8%. Using a comprehensive annual calculation of BUMD has reached the level of effectiveness with a value of 100%. Tujuan penelitian ini untuk mengetahui tingkat efisiensi dan hasil yang mencerminkan kinerja dan kinerja keuangan BUMD di Kota Semarang, periode 2014-2016. Jenis data yang digunakan adalah data sekunder, menggunakan analisis data melalui analisis DEA dan metode wawancara. Hasil penelitian menunjukkan bahwa PDAM dan RPH & BPH pada tahun 2014 masih memenuhi level, dengan nilai 82,4% dan 62,6%. Pada 2015, secara keseluruhan, BUMD telah mencapai nilai efisiensi dan efektifitas. Pada 2016, perusahaan RPH & BPH belum dapat mencapai level 8,1%. Tingkat banding di BPR BKK 2014 dan 2015 akan bersama-sama mencapai tingkat pencapaian bersama sebesar 89,5% dan 93,8%. Menggunakan perhitungan tahunan BUMD yang komprehensif telah mencapai tingkat efektifitas dengan nilai 100%.